Low temperature synthesis of high alumina cements by novel Co-melt precursors and their implementation as castables with some micro fine additives - Kumar V.; Singh V.K.; Srivastava A. (My University, 2025)
In the present investigations nano size high alumina cements (HAC) were prepared by very effective co-melt precursor sintering technique from their metal nitrate precursors. The prime cementing phases observed were CA, CA 2, and C12A7. The addition of nano structured cements in refractory castables has improved the thermo-chemical-mechanical properties to a significant extent. Each batch of low cement castables (LCC) was prepared from calcined Chinese bauxite, HAC, and superfine additives. The effect of HAC in bauxite castable with the additives similar to Silicon Carbide, reactive alumina, and micro-fine silica on the sinterability and properties of these castables was investigated. Physical properties such as apparent porosity and bulk density, mechanical properties such as hot modulus of rupture (HMOR), cold and hot modulus of rupture (CMOR), and cold crushing strength (CCS) of hydrated and sintered castables were studied. The sintered castables were also characterized for their solid phase compositions and microstructure using X-ray diffraction (XRD) and FE-SEM, respectively. In the castables new phases such as mullite, α-alumina were formed at the expense of bauxite and silica. Solid solution of mullite formed at high temperature acts as a bonding phase and is accounted for high HMOR, CMOR, and CCS values. These excellent properties of such castables may enable their uses in various applications such as refractory lining for fabrication of steel, aluminium, copper, glass, cement, chemicals, and ceramics. © 2013 The American Ceramic Society.